The Effectiveness of Using the Focusky Application on the Indonesian Language Learning Outcomes of Grade VII Students at SMPN 3 Pitu Riase, Sidenreng Rappang - Muh Aidil; Abd. Kahar; Madaling Madaling; Syamsunir Syamsunir (Edumaspul: Jurnal Pendidikan, 2025)
This study aims to determine the extent to which the Focusky application influences the Indonesian language learning outcomes of Grade VII students at SMPN 3 Pitu Riase. The research employed a quantitative deductive methodology. This type of research used a one-group pretest-posttest design and was quasi-experimental in nature. Instead of using a control group, the study examined students’ learning outcomes before and after using the Focusky media. Pretest and posttest assessments were used to collect the data.The findings of the study revealed that students’ scores improved after using the Focusky media. In the posttest, the highest score increased to 90 and the lowest to 45, while in the pretest, the highest score was 55 and the lowest was 25. These results indicate that the use of the Focusky application can enhance students’ learning outcomes. Therefore, it can be concluded that the Focusky application effectively improves students’ achievement in Indonesian language learning.